Dance Media Collaborations: Engaging "At Risk" Youth. Issue 2 (2nd April 2016) - Parkins, Chell
ABSTRACT: This article presents strategies I developed to engage my students in collaborative, project-based dance units using video and social media at a Title 1 high school in rural Texas. The school has a history of violence, and students also face many challenges in their personal lives. I found that through dance and video, students could express and process some of their ongoing struggles as well as develop support systems among themselves that would extend far beyond the dance projects. At the same time, they were developing twenty-first-century skills with the use of video, video editing, and social media. The projects described in this article could serve as models for other dance teachers in working with their students .